AB0319 ABATACEPT IN RHEUMATOID ARTHRITIS WITH INTERSTITIAL LUNG DISEASE. A MULTICENTRE STUDY OF 181 PATIENTS. (June 2019) - Fernández-Díaz, Carlos; Loricera, J.; Castañeda, Santos; Juan-Mas, A.; Carrasco-Cubero, Carmen; Casafont-Solé, Ivette; Almodovar, Raquel; Alvarez-Rivas, Noelia; Cros, Clara Aguilera; Villa-Blanco, Ignacio; Ordoñez, Sergi; Romero-Yuste, Susana; et al.
Abstract : Background: Interstitial Lung Disease (ILD) is a severe extraarticular manifestation of rheumatoid arthritis (RA). Objectives: Our aim was to assess the efficacy of abatacept (ABA) in RA patients with ILD. Methods: Retrospective multicenter study of RA patients with ILD treated with ABA. ILD was diagnosed by HRCT. We have analyzed the following variables: a) 1-point change the Modified Medical Research Council (MMRC); b) FVC improvement ≥10%; and improvement ≥10% in DLCO; c) radiological improvement in HRCT scan, d) changes in DAS28 score. Values were compared with baseline e) prednisone doses Results: We studied 181 patients (94women/87 men) with ILD associated to RA. The follow-up was 12.1[6.2-24.1] months. The mean age was 64.54 ± 9.7 years. The median to progression of ILD was 12 [3-43.75] months. 81 patients were treated in monotherapy, 100 patients in combination therapy. The most frequent pattern was UIP 45, 3%. The most of patients who did not have dyspnea remained asymptomatic. See results in Figure1 . DAS28 also improved. We appreciate a decrease in the dose of prednisone compared to the initial dose. Conclusion: ABA seems to be effective. However, should be verified in prospective and randomized studies. Disclosure of Interests: Carlos Fernández-Díaz Speakers bureau: Bristol-Myers, J. Loricera: None declared, Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, A. Juan-Mas: None declared, Carmen Carrasco-Cubero: None declared, Ivette Casafont-Solé: None declared, RAQUEL ALMODOVAR: None declared, Noelia Alvarez-Rivas: None declared, CLARA AGUILERA CROS: None declared, Ignacio Villa-Blanco: None declared, Sergi Ordoñez : None declared, Susana Romero-Yuste: None declared, C. Ojeda-Garcia: None declared, Manuel Moreno : None declared, I. Hernández-Rodriguez: None declared, M. López-Corbeto: None declared, Maria Lopez Lasanta: None declared, Francisco Ortiz-Sanjuán: None declared, B. Alvarez-Rodríguez: None declared, A. Ruibal-Escribano: None declared, Rosa Expósito: None declared, M. Retuerto-Guerrero: None declared, Trinidad Pérez Sandoval: None declared, Alejandra López Robles: None declared, Patricia Carreira: None declared, Natalia Mena-Vázquez: None declared, ANA URRUTICOECHEA-ARANA: None declared, C. Delgado-Beltran: None declared, José Luis Andréu Sánchez: None declared, Alejandro Olive: None declared, S, Rodriguéz-Muguruza: None declared, José Antonio Bernal-Vidal: None declared, E.C. Cervantes Pérez : None declared, Olga Maiz-Alonso Speakers bureau: Pfizer, R. Castellanos-Moreira: None declared, S Rodiguéz-Garcia: None declared, I. Cabezas-Rodriguez: None declared, Mireia Moreno : None declared, Ivan Castellví Consultant for: I received fees less than 5000USD as a consultant for Kern and Actelion, Paid instructor for: I received fees less than 2000USD as a instructor for Boehringer -Ingelheim, Novartis and Gebro, Speakers bureau: ND, Luis Marcelino Arboleya Rodríguez: None declared, C. González-Montagut Gómez: None declared, Blanca Garcia-Magallon: None declared, E. Salgado-Pérez: None declared, M. Rodíguez-Gómez: None declared, C. Fito-Manteca: None declared, J M Blanco: None declared, DESEADA PALMA SANCHEZ: None declared, Paloma Vela-Casasempere Grant/research support from: UCB, Abbvie, Pfizer, Roche, Bristol-Myer-Squibb (another research, not BIOBADASER related), Consultant for: UCB, Lilly, Pfizer, Roche, Bristol-Myer-Squibb, Speakers bureau: Roche, UCB, MSD, Pfizer, GSK, BMS, Lilly, Gemma Bonilla: None declared, R. López-Sánchez: None declared, J. Fernández-Melon: None declared, Cristina Hidalgo: None declared, Miguel A González-Gay Grant/research support from: Prof. MA Gonzalez-Gay received grants/research supports from Abbvie, MSD, Jansen and Roche., Speakers bureau: Consultation fees/participation in company sponsored speaker's bureau from Pfizer, Lilly, Sobi, Celgene, Novartis, Roche and Sanofi., Ricardo Blanco Grant/research support from: Abbvie, MSD, and Roche, Consultant for: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Speakers bureau: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen